SYNTHESIS AND STRUCTURE OF URANYL NITRATE WITH BIS(N,N’-DIETHYLAMIDE) (N’’-α-METHYLPIROL-CARBOXAMIDE)-THREEAMIDEPHOSPHATE: UDC 541.49+546.65 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
Coordination compound UO2(HL)2(NO3)2, were HL – bis(N, N'-diethylamido) (N''-α-methylpirrole-carboxamido)-triamidophosphate, have been synthesized and investigated. Structure of UO2(HL)2(NO3)2 was solved by X-ray diffraction method. It was determined, that ligands are included in coordination sphere of complex in molecular form monodenticaly via oxygen atom of phosphoryl group. Coordination number of central uranium atom is equal to 8: 2 О (of HL ligands) + 4 О (of two bidantate cyclic coordinated nitrate groups) + 2 O (oxoligands). Coordination polyhedron can by characterized as hexagonal bipyramide.
Keywords: -